2019
DOI: 10.1007/s40262-019-00834-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Acting Insulin Aspart: A Review of its Pharmacokinetic and Pharmacodynamic Properties and the Clinical Consequences

Abstract: Fast-acting insulin aspart (faster aspart) is insulin aspart (IAsp) with two added excipients, l-arginine and niacinamide, to ensure formulation stability with accelerated initial absorption after subcutaneous administration compared with previously developed rapid-acting insulins. The pharmacokinetic/pharmacodynamic properties of faster aspart have been characterised in clinical pharmacology trials with comparable overall methodology. In subjects with type 1 (T1D) or type 2 (T2D) diabetes, the serum IAsp conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
3
23
0
5
Order By: Relevance
“…Similarity was observed between AT247, IAsp, and faster IAsp in overall insulin exposure and overall glucose-lowering effect. This is also in accordance with the results of the pooled pharmacological analyses of faster IAsp versus IAsp ( 31 , 32 ) and confirms that the glucose-lowering potency is maintained and that only the time-concentration and time-action profiles are favorably changed.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similarity was observed between AT247, IAsp, and faster IAsp in overall insulin exposure and overall glucose-lowering effect. This is also in accordance with the results of the pooled pharmacological analyses of faster IAsp versus IAsp ( 31 , 32 ) and confirms that the glucose-lowering potency is maintained and that only the time-concentration and time-action profiles are favorably changed.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to these second-generation insulin analogs, AT247 exhibited a faster offset of exposure by a left-shift of the late part of the pharmacokinetic time profile compared with IAsp and faster IAsp. The accelerated clearance of faster IAsp versus IAsp has already been well described ( 31 , 32 ). These reports showed that offset of faster IAsp was 12 min earlier than for IAsp ( P < 0.001), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A statistically significant reduction in 2-hour postprandial glycemia after standardized meal was reported. 26,27 However, due to regulatory approval and availability the common use in clinical practice is limited. Lujif et al…”
Section: Discussionmentioning
confidence: 99%